Isolation and sequence determination of the 3′-terminal regions of isotopically labelled RNA molecules - Rosenberg, Martin (1974)
The method which was developed for the selective isolation of 3′-terminal polynucleotides from large RNA molecules on columns of cellulose derivatives containing covalently bound dihydroxyboryl groups has been modified and adapted for use on radioactively labelled RNAs. The 3′-terminal polynucleotide fragments which result from specific ribonuclease digestion of isotopically detectable quantities of RNA can be selectively obtained in both high yield and purity by the modified procedure and can be subsequently analyzed by standard electrophoretic and chromatographic techniques. In addition, when the extent of enzymatic fragmentation of the RNA is controlled, the procedure permits the selective isolation of discrete “sets” of fragments of variable chain length, all of which derive from the 3′-terminus of the RNA molecule. These overlapping polynucleotides can be used directly to obtain extensive sequence information regarding the primary structure in the 3′-region of the RNA.